2017
DOI: 10.1002/adma.201704681
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancies Dominated NiS2/CoS2 Interface Porous Nanowires for Portable Zn–Air Batteries Driven Water Splitting Devices

Abstract: The development of highly active and stable oxygen evolution reaction (OER) electrocatalysts is crucial for improving the efficiency of water splitting and metal-air battery devices. Herein, an efficient strategy is demonstrated for making the oxygen vacancies dominated cobalt-nickel sulfide interface porous nanowires (NiS /CoS -O NWs) for boosting OER catalysis through in situ electrochemical reaction of NiS /CoS interface NWs. Because of the abundant oxygen vacancies and interface porous nanowires structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
392
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 584 publications
(419 citation statements)
references
References 57 publications
15
392
1
2
Order By: Relevance
“…[35,36] The catalytic ability of electrocatalysts varies with the particle size and morphology. [38][39][40] In accordance with the Brewer hypo-hyper-d-electronic theorya nd the volcano plot of electrocatalytic activity, [41,42] we Faceted nanomaterials with highly reactive exposed facets have been the target of intense researches owing to their significantly enhanced catalytic performance. [38][39][40] In accordance with the Brewer hypo-hyper-d-electronic theorya nd the volcano plot of electrocatalytic activity, [41,42] we Faceted nanomaterials with highly reactive exposed facets have been the target of intense researches owing to their significantly enhanced catalytic performance.…”
Section: Introductionmentioning
confidence: 75%
“…[35,36] The catalytic ability of electrocatalysts varies with the particle size and morphology. [38][39][40] In accordance with the Brewer hypo-hyper-d-electronic theorya nd the volcano plot of electrocatalytic activity, [41,42] we Faceted nanomaterials with highly reactive exposed facets have been the target of intense researches owing to their significantly enhanced catalytic performance. [38][39][40] In accordance with the Brewer hypo-hyper-d-electronic theorya nd the volcano plot of electrocatalytic activity, [41,42] we Faceted nanomaterials with highly reactive exposed facets have been the target of intense researches owing to their significantly enhanced catalytic performance.…”
Section: Introductionmentioning
confidence: 75%
“…[28][29][30] In addition, to properly make use of the intrinsic advantage of BSs, a novel fabrication approach is to directly grow the electrically conductive BSs on N-doped carbon materials (BSs@NMSs), which would ensure with a better contact with the conductive matrix. This will be in contrast to those processes completed at high hydrothermal temperatures [28,29,31,32] or chemical vapor deposition (CVD; they are usually higher than 600 °C), [33,34] which are tedious and time consuming. This will be in contrast to those processes completed at high hydrothermal temperatures [28,29,31,32] or chemical vapor deposition (CVD; they are usually higher than 600 °C), [33,34] which are tedious and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…[31] In particular, it would be further desirable to develop the sulfide phase at a low temperature, ideally at room temperature. Most importantly, the mechanical strength of BSs@NCMs-based electrodes is heat sensitive and easily damaged to lose flexibility in these processes, [31,32] thus also hinder its large-scale application of flexible ZABs in portable and wearable electronic devices. Most importantly, the mechanical strength of BSs@NCMs-based electrodes is heat sensitive and easily damaged to lose flexibility in these processes, [31,32] thus also hinder its large-scale application of flexible ZABs in portable and wearable electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Selective control of the crystal structure is another effective way. [13] Despite so much progress in separately regulating these factors (exfoliation, phase transformation, and surface engineering) for better catalytic activity,there have not been reports on efficient integration of them in one material system, which is believed to allow the optimal chemical and electronic structure toward the OER to be achieved.Herein, we report the successful integration of exfoliation, cubic-to-orthorhombic phase transformation, and surface oxidative reorganization in cobalt diselenide (CoSe 2 )through aconvenient Ar/O 2 plasma method (Scheme 1). [9] Although cubic-to-orthorhombic (c-to-o) transition has been described through at hermal method [10] and the reverse change theoretically can be realized by rotating half of the X 2 2À groups, [11] there is still lack of facile means to actually establish this conversion from pyrites to marcasites at present.…”
mentioning
confidence: 99%
“…[9] Although cubic-to-orthorhombic (c-to-o) transition has been described through at hermal method [10] and the reverse change theoretically can be realized by rotating half of the X 2 2À groups, [11] there is still lack of facile means to actually establish this conversion from pyrites to marcasites at present. [13] Despite so much progress in separately regulating these factors (exfoliation, phase transformation, and surface engineering) for better catalytic activity,there have not been reports on efficient integration of them in one material system, which is believed to allow the optimal chemical and electronic structure toward the OER to be achieved. [12] Early studies have revealed that the formation of ah eterojunction metal dichalcogenide/oxide interface can significantly improve the relevant OER energetics,yet precise controllability is hard to realize.…”
mentioning
confidence: 99%